2013
DOI: 10.1002/ar.22562
|View full text |Cite
|
Sign up to set email alerts
|

Airway Morphology From High Resolution Computed Tomography in Healthy Subjects and Patients With Moderate Persistent Asthma

Abstract: Models of the human respiratory tract developed in the past were based on measurements made on human tracheobronchial airways of healthy subjects. With the exception of a few morphometric characteristics such as the bronchial wall thickness (WT), very little has been published concerning the effects of disease on the tree structure and geometrical features. In this study, a commercial software package was used to segment the airway tree of seven healthy and six moderately persistent asthmatic patients from hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 58 publications
1
13
0
Order By: Relevance
“…The HR for the major and minor daughters was measured to be HR maj = 0.914±0.087 and HR min = 0.663±0.184. The former is only marginally lower to the one predicted by Tawhai et al [31] while HR min is almost identical to the results of both [31] and [34]. Finally, in their implementation of the model, [32] calculated min and max HR of 0.81 and 0.85, with zero std.…”
Section: Resultssupporting
confidence: 62%
See 4 more Smart Citations
“…The HR for the major and minor daughters was measured to be HR maj = 0.914±0.087 and HR min = 0.663±0.184. The former is only marginally lower to the one predicted by Tawhai et al [31] while HR min is almost identical to the results of both [31] and [34]. Finally, in their implementation of the model, [32] calculated min and max HR of 0.81 and 0.85, with zero std.…”
Section: Resultssupporting
confidence: 62%
“…Montaudon et al [53] found this value to vary between 0.65 and 0.97 while [34] measured HR = 0.72 for the first 6 generations. The HR for the major and minor daughters was measured to be HR maj = 0.914±0.087 and HR min = 0.663±0.184.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations